2016
DOI: 10.1016/j.appet.2016.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Providers’ response to child eating behaviors: A direct observation study

Abstract: Child care providers play an important role in feeding young children, yet little is known about children’s influence on providers’ feeding practices. This qualitative study examines provider and child (18 months -4 years) feeding interactions. Trained data collectors observed 200 eating occasions in 48 family childcare homes and recorded providers’ responses to children’s meal and snack time behaviors. Child behaviors initiating provider feeding practices were identified and practices were coded according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 61 publications
3
35
0
2
Order By: Relevance
“…There were eleven cross-sectional studies [ 16 , 17 , 19 , 20 , 22 , 23 , 25 , 26 , 29 32 ], one observational study [ 27 ], one study used accelerometers [ 21 ], and four studies used qualitative methods [ 18 , 24 , 28 , 33 ]. Eight studies focused solely on FCCHs or FCCH providers, meaning these studies did not include other types of child care facilities [ 16 , 18 , 21 , 24 , 27 30 ]. Five studies examined both the nutrition and physical activity environment [ 19 , 20 , 26 , 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were eleven cross-sectional studies [ 16 , 17 , 19 , 20 , 22 , 23 , 25 , 26 , 29 32 ], one observational study [ 27 ], one study used accelerometers [ 21 ], and four studies used qualitative methods [ 18 , 24 , 28 , 33 ]. Eight studies focused solely on FCCHs or FCCH providers, meaning these studies did not include other types of child care facilities [ 16 , 18 , 21 , 24 , 27 30 ]. Five studies examined both the nutrition and physical activity environment [ 19 , 20 , 26 , 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Five studies examined both the nutrition and physical activity environment [ 19 , 20 , 26 , 29 , 30 ]. Four studies focused only on the nutrition environment [ 22 , 23 , 27 , 31 ] while two focused solely on the physical activity environment [ 21 , 25 ]. Six studies examined TPB related beliefs [ 16 , 18 , 24 , 28 , 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Future studies are needed to determine the impact of responsive feeding practices on child outcomes across childcare contexts as well as child characteristics that may lead to the use of more responsive feeding practices. For example, children's acceptance of food is related to childcare providers using more responsive feeding practices (Tovar et al, 2016). It is also recommended that future studies focus on determining if training child care providers in nutrition and childhood obesity prevention strategies influences their implementation of responsive feeding practices.…”
Section: Discussionmentioning
confidence: 99%
“…This same survey also showed that while most providers sat with children during meals, few ate the same foods as children, thus missing out on an important opportunity for role modeling. An observational study of family child care homes in Rhode Island found that providers often offered positive reinforcement in response to children’s acceptance of food; however, providers also responded with controlling practices when children requested second helpings of food (Tovar et al, 2016). The low number of studies conducted with family child care homes highlights the need to conduct both observational and intervention research in this area to help improve foods and beverages served and mealtime feeding practices.…”
Section: Introductionmentioning
confidence: 99%